2016
DOI: 10.4103/1735-3327.182182
|View full text |Cite
|
Sign up to set email alerts
|

A finite element study of teeth restored with post and core: Effect of design, material, and ferrule

Abstract: Background:Different postdesigns and materials are available; however, no consensus exists regarding superiority for stress distribution. The aim of this study was to evaluate the effect of design and material of post with or without ferrule on stress distribution using finite element analysis.Materials and Methods:A total of 12 three-dimensional (3D) axisymmetric models of postretained central incisors were made: Six with ferrule design and six without it. Three of these six models had tapered posts, and thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 21 publications
1
23
0
2
Order By: Relevance
“…Similar study also revealed that less amount of dentinal stress in fiberreinforced composite core as compared to other system [13]. However, role of incorporation of ferrule could not be overlooked to minimize the stress [13,14].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar study also revealed that less amount of dentinal stress in fiberreinforced composite core as compared to other system [13]. However, role of incorporation of ferrule could not be overlooked to minimize the stress [13,14].…”
Section: Discussionsupporting
confidence: 62%
“…First, the endodontic treatment was carried out in all of her traumatized teeth [11][12][13][14] then the radiographs were taken ( Figures 3 and 4). The tooth with greatest loss of coronal tooth structure [12] was judged to be a candidate for post-and-core restoration.…”
Section: Case Presentationmentioning
confidence: 99%
“…with possibility of re-intervention and preservation of the tooth 4 . These findings may also be associated with the presence of a ferrule, which has a protective effect since it improves the mechanical behavior of pulpless teeth by reducing cervical stress level on the restored root 14,16 . Other studies have shown that the ferrule effect provided by remaining dentin is associated with restorable failure modes [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a cervical ferrule positively affects the stress distribution pattern by reducing stress concentration on the root and risk of tooth fracture. Finite element analysis shows that the ferrule effect attenuates stress intensity on the root when either metal or fiber posts are used [12][13][14][15] . Previous studies also did not find a difference in fracture resistance between teeth restored with crowns and cast and post cores or fiber posts when a ferrule was present 13,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Fiber reinforced composite post (FRC) and composite resin core recorded minimal stresses within the post but the stresses transmitted to cervical dentin were more as compared to other systems. Minimal stresses in cervical dentine were observed where the remaining coronal dentin was strengthened by ferrule [13]. The position of the tooth in the arch, ferrule size, proximal contact, periodontal support and restoration type are survival prediction factors that should be considered when performing post-endodontic restoration [14].…”
Section: And 4)mentioning
confidence: 99%